Association between Self-Reported Fatigue and Sarcopenia Measures among Elderly in Selangor, Malaysia - Justine, Maria; Latir, Aliff; Noor, Nadhirah; Joanny, Angelbeth; Iskandar, Izzaty; Amirul Faizi, Maisarah Sakinah; Edinan, Dzulhelmi (Kesmas, 2021)
The association between fatigue and sarcopenia is not well understood, therefore, this study aimed to compare the sarcopenia measures among elderly with mild and severe fatigue and to determine whether fatigue severity is associated with sarcopenia measures. This was a cross-sectional study conducted on201 elderly (age = 68.45±6.30 years). The elderly was classified into either mild or severe fatigue based on the Fatigue Severity Scale (FSS), meanwhile, sarcopenia measures include SARC-F score, muscle mass (ASM/height2), calf circumference (CC), upper (handgrip) and lower limb muscle strength, as well as physical performance (gait speed). Data were analyzed using independent t-tests and logistic regression. The results showed that elderly with severe fatigue were significantly older, with lower muscle strength, and slower gait speed (all p-value <0.05). After adjusting for age, fatigue severity remained significantly associated with SARC-F score (OR = 1.583, 95% CI = 1.262-1.986, p-value = 0.001) and CC (OR = 1.103, 95% CI = 1.014-1.200, p-value = 0.022). Moreover,when the SARC-F score was removed from the regression model, fatigue severity was significantly associated with CC (OR = 1.088, 95% CI = 1.006-1.178, p-value = 0.036) and gait speed (OR = 0.011, 95% CI = 0.001-0.168, p-value = 0.001). Based on the results, fatigue severity is associated with SARC-F score, CC, and gait speed, therefore, interventions targeted at sarcopenia measures is recommended to optimize physical endurance in the elderly.